CONTENT AND FEATURES OF CORRECTIVE WORK WITH CONVICTS OF CRIMES AGAINST PUBLIC ORDER AND MORALITY (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the study of the content and features of correctional work with those who have been convicted of crimes against public order and morality. The authors analyzed modern approaches to the problem and the state of scientific research on the procedure for applying and the influence of correctional programs on the possibility of convicts returning to self-directed, obedient behavior. On the basis of the conducted analysis, a methodology for diagnosing generalized semantic attitudes of offenders and instructions for its use were developed and proposed for implementation, which allows specifying a further set of measures for the social rehabilitation of persons convicted of crimes against public order and morality. The study lays the foundation for scientific research in the field of social rehabilitation of convicts. The results of the published work will be useful for practical application by employees of penal institutions and the probation service of Ukraine and can serve as a starting point for further work on improving and expanding correctional practices.
Keywords: social rehabilitation; correctional programs; programs of differentiated educational influenc; public order and morality; convicts, radicalism; resocialization; correction